Substrate Partitioning Scheme for Compact Charge Modeling of Multigate MOSFETs - Sung-Min Hong; Junsung Park (IEEE Journal of the Electron Devices Society, 2017)
A modeling approach for the charge-voltage characteristics of multigate metal-oxide-semiconductor field-effect transistors with complicated cross sections is proposed. Using solutions of linear equations, the substrate region is partitioned into several 1-D MOS structures and the coupling capacitances between these structures are evaluated. It is numerically demonstrated that the set of 1-D MOS structures together with the coupling capacitances yields excellent agreement in the charge-voltage characteristics in all operational regimes. Moreover, further simplification allows us to model the charge-voltage characteristics accurately with only two MOS structures.